2015
DOI: 10.5761/atcs.oa.13-00283
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aortic Cross-Clamping Time on Peripheral Nerves: Experimental Model

Abstract: Purpose: The present study investigated the correlation between extend aortic cross-clamping time and peripheral nerve injury on rats. Methods: 24 male, Sprague Dawley rats were divided into 3 groups; (a) control group: abdomen was directly closed after reached aorta, and followed by 72 hours, (b) shortterm ischaemia-reperfusion group: peripheral nerve ischemia was induced in rats by supraceliac aortic occlusion for 20 min followed by 72 h of reperfusion, (c) long-term ischaemia-reperfusion group: peripheral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition to these histopathological finding, syringic acid decreased the MDA levels and increased the SOD and NRF-1 activities in biochemical analysis reducing oxidative stress after ischemia. Akdemir et al reported that aortic clamping resulted in increase in MDA levels in peripheral nerves and edema that leads to axonal injury and myelin damage (2). The occurrence of IFD and edema indicates that long-term ischemia/reperfusion has a devastating impact on the peripheral neurons and that there is a direct link between paraplegia, one of the most common postoperative complications of aorta surgery, and the cross-clamping.…”
Section: █ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these histopathological finding, syringic acid decreased the MDA levels and increased the SOD and NRF-1 activities in biochemical analysis reducing oxidative stress after ischemia. Akdemir et al reported that aortic clamping resulted in increase in MDA levels in peripheral nerves and edema that leads to axonal injury and myelin damage (2). The occurrence of IFD and edema indicates that long-term ischemia/reperfusion has a devastating impact on the peripheral neurons and that there is a direct link between paraplegia, one of the most common postoperative complications of aorta surgery, and the cross-clamping.…”
Section: █ Conclusionmentioning
confidence: 99%
“…Eventually, this fatal cascade leads to formation of MDA as the end product of lipid peroxidation and at the same time is considered as one of the most sensitive markers of lipid peroxidation. Akdemir et al (2) reported that aortic clamping resulted in increase in MDA levels in peripheral nerves and edema that leads to axonal injury and myelin damage. Syringic acid may enable neural tissues to become more resistant to lipid peroxidation, thereby activating antioxidant enzymes.…”
Section: █ Conclusionmentioning
confidence: 99%